A small signal coupling model for predicting the coupling between LNAs *Project supported by the National Natural Science Foundation of China (No. 61401025). (July 2017) - Shi, Junyu; Cui, Dasheng; Wu, Yuming
Abstract: A small signal coupling model is developed to analyze the coupling between two LNAs. The mutual inductance between the adjacent on-chip inductors is considered responsible for this coupling. A set of formulas have been derived to quantitatively predict the coupling effects. Based on our analysis, a quick estimation can be made to see which pair of inductors plays a key role in evaluating the coupling between the LNAs. Source inductors of two LNAs are placed closely while the load inductors are far apart according to the analysis. To validate the proposed theory, two 2 GHz LNAs are fabricated. The LNAs have a peak gain of 18 dB and NF of 1.4 dB. The coupling between the LNAs is −30 dB.